Soviet Lithuanians, Amber and the "New Balts": Historical Narratives of National and Regional Identities in Lithuanian Museums, 1940–2009 - Rindzevičiute, Egle (Culture Unbound, 2010)
In the twentieth century Lithuania emerged from the crumbling Russian Empire as a post-colonial nationalising state. Its short-lived independence (1918–1940) featured attempts to assemble the material foundations for an imagined community of Lithuanians, however in 1940 this nationalist project was disrupted by Soviet occupation. However, this article argues that regardless of the measures taken against political nationalism by the Soviets, the material work of assembling the Lithuanians as a historical and ethnic nation was not abandoned. The study analyses the ways in which Northern and Baltic categories were used to regionally situate the ethnic identification of the Lithuanian population in Soviet and post-Soviet Lithuanian museums. The cases of the Historical-Ethnographic Museum and the Museum of Amber reveal that Northern and Baltic dimensions had to be reconciled with the Soviet version of the Lithuanian past. The resulting assemblage of Lithuania as a synchronic and diachronic community of inhabitants who defined themselves through shared Baltic ancestors and centuries-old uses of amber was transmitted to the post-Soviet museums. The most salient post-Soviet changes were, first, the rewriting of the relations between Lithuanians and the Nordic countries in positive terms and in this way reversing the Soviet narrative of Lithuania as a victim of aggression from the North. Second, the Soviet construction of amber as a material mediator which enabled Lithuanians to connect with each other as a synchronic and diachronic imagined community was somewhat pushed aside in favour of the understanding of amber as a medium of social and cultural distinction for the ancient Balts and contemporary Lithuanian elites.